Analisis Kesadaran Perpajakan, Sanksi Perpajakan, Kualitas Pelayanan Perpajakan, Tingkat Pendidikan, dan Gender Terhadap Kepatuhan Wajib Pajak di KPP Pratama Batam Selatan - Helen Helen; Neni Marlina Br Purba (Universitas Batanghari, 2023)
The country's largest source of income is taxation, which is used to pay for all routine expenditures as well as national development. Thus, it can be said that the process of national development will not run smoothly without maximum tax revenue. Taxpayer compliance is closely related to tax revenue, because an increase in taxpayer compliance can result in an increase in tax revenue. However, it was found that the level of compliance of individual taxpayers registered at KPP Pratama Batam Selatan was still low in fulfilling existing tax obligations. There are a number of factors that influence the compliance of individual taxpayers in carrying out their tax obligations. The aim of this research is to know and analyze the effect of tax awareness, tax sanctions, quality of tax services, education level, and gender on individual taxpayer compliance at KPP Pratama South Batam. Primary data was used in this study from respondents by distributing questionnaires via Google Form online. The sample collection used the purposive sampling method, and used the slovin formula so that a total of 100 respondents were obtained. Descriptive analysis techniques, data quality tests (reliability and validity), classical assumption tests, multiple linear regression analysis, and hypothesis testing (coefficient of determination, partial, simultaneous) were used in this study. The results show that partially awareness of taxation, tax sanctions, and quality of tax services have a significant effect on individual taxpayer compliance at KPP Pratama Batam Selatan, while education level and gender have no significant effect. Furthermore, it is known that simultaneously tax sanctions, tax awareness, level of education, quality of tax services, and gender have a significant influence.